Metastatic squamous cell non-small-cell lung cancer (NSCLC): disrupting the drug treatment paradigm with immunotherapies - Sarah L Scarpace (BioExcel Publishing Ltd, 2015)
Lung cancer is the third most commonly diagnosed cancer and the leading cause of cancer-related death in the United States. Unlike non-squamous NSCLC, squamous NSCLC rarely harbor epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) mutations for which there are directed therapies, and until the recent approval of immunotherapies for squamous NSCLC, a limited number of traditional cytotoxic chemotherapy drugs have been FDA-approved for use in the treatment of advanced and metastatic squamous NSCLC. Immunotherapies directed at the programmed cell death-1 receptor (PD-1) or its ligand (PD-L1) (nivolumab and pembrolizumab) have demonstrated efficacy in both nonsquamous and squamous cell NSCLC. Because of their similar mechanism of action against the PD-L1/PD-1 pathway, both drugs have similar toxicity profiles related to immune-mediated adverse reactions that can generally be monitored and managed with oral corticosteroids. This paper provides an overview of drug therapy options for squamous cell NSCLC with a focus on the evidence and clinical application of the anti-PD1 therapies. A comparison of the dosing, administration, indications, and differences in the measurement of PD-L1 expression in the clinical trials of nivolumab and pembrolizumab is also provided.